Design and Development of Vegetable Seller’s Bike by Using Anthropometry Approach and Quality Function Deployment Method (QFD) - Fahmi Hidayati; Irwan Iftadi; Taufiq Rochman (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2013)
“Pedagang Kaki Lima” (PKL) give contribution on absorption of unempolyment, improvement of seller’s walfare, and ease of fulfillment public consumption. In fact, many “pedagang kaki lima” were not considered, the example is around vegetable seller. That is about suitable of transportation to go around vegetable seller, especially to go around vegetable seller by using bike. There is complaint about their’s bike. The point of that complaint is their health. Whereas, the health must be kept in order to be always healthy and do good work. So, it needed design of bike suitable for the consumer needs, ergonomic, and safety of falling from bike in order to keep their health. In making that bike design it is used Quality Function Deployment Method. That method is used to design of bike based on the voice of customer. Besides using QFD method, it is also used anthropometry approach. The design which choosen in this research is C design. It has specifications using roller bearing, quantity of serration is 50 serration in chainwheel and 24 serration in cassette, material of velk is aluminum alloy, maximal wide of wheel is 4,5 cm, dimension of handle bar is 38,4 cm for lenght and 10,9 cm for lenght of handful, distance from handle bar to land is 92 cm, distance from handle bar to saddle is 448,4 cm, dimension of front basket is 113 cm for lenght, 63 cm for wide, 60 cm for high and dimension of back basket is 113 cm for lenght, 25 cm for wide, 45 cm for high, and the last is quantity of wheel is 4.